An efficient oxidative conversion of 2-aryl-2H-chromenes to the corresponding flavones by tert-butylhydroperoxide and copper bromide. Issue 15 (13th April 2016) - Banerjee, Dipanwita; Kayal, Utpal; Maiti, Gourhari
Graphical abstract: Highlights: A simple and an efficient oxidative conversion of chromenes to flavones. A very short reaction time and high level of functional group tolerance. Non precious metal salt, Cu(II) bromide is used as a catalyst. Wide applicability (21 examples) and good to excellent yields (67–94%). Abstract: A simple and efficient method has been developed for the facile oxidation of chromenes to the corresponding flavones by tert -butylhydroperoxide (TBHP) in the presence of copper(II) bromide catalyst in toluene at 80 °C in a very short time. The reaction demonstrates excellent reactivity, functional group tolerance, and good to excellent yields without using conventional strong oxidizing agents.